Negócio ou estratégia?: um estudo de caso sobre negócios jurídicos processuais e comportamento judicial autocontido. - Lima, Luís Daniel Alves (2020)
How are procedural legal businesses being used by judicial organs? This study aims to investigate the initiative/incentive of the judicial organ in proposing procedural agreements during the judicial procedure. This research is justified due to the lack of empirical studies that investigate data on the use of procedural legal businesses. For the construction of the hypothesis, it is observed that passive virtues / formal arguments are used in order to exempt the decision-making of the judicial organs on costly situations. In view of this note, the hypothesis of the procedural legal businesses proposed, signed or encouraged by judicial organs, during the process, is to indicate a self-contained judicial strategy as a way of avoiding decision-making involving situations of high tension. The methodology used in the present research fled from pure dogmatics, to empirically investigate the use of procedural legal businesses by the courts. The operation took place using the methodological tool “case study”. As an analysis parameter, the following investigative criteria are used: a) existence of a lato sensu legal business; b) business proposition initiative; c) procedural business requirements; d) compliance with the business; e) type of sentence; f) provisional decision; g) quality of applicants; h) time; i) economic and social conditions. As a result of this research, it was obtained that, in the analyzed process, the proposition of the procedural legal business by the judicial organ was the basis for a self-contained strategic posture. It is concluded, therefore, that the procedural legal business signed, proposed or encouraged by the court during the process is a strategic indicator.